Improving Access to Finance for India's Rural Poor - Basu, Priya (Washington, DC: World Bank, 2012)
Improving Access to Finance for India's Rural Poor examines the current level and pattern of access to finance for India's rural households, evaluates various approaches for delivering financial services to the rural poor, analyzes what lies behind the lack of adequate financial access for the rural poor, and identifies what it would take to improve access to finance for India's rural poor. Based on the analysis of a large-scale rural household survey, in combination with an evaluation of the role of financial markets and institutions, this title also examines different forms of financial service provision, including formal, informal and microfinance, raises questions about approaches used so far to address financial exclusion, and makes recommendations for policy advisors and financial service providers on how to scale-up access to finance for India's rural poor, to meet their diverse financial needs (savings, credit, insurance against unexpected events, etc.), in a commercially sustainable manner. Its conclusions will be of interest to anyone involved in economic policy, finance or microfinance, poverty analysis, and poverty reduction.